2007
DOI: 10.1254/jphs.fp0061088
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of the Methanol Extract of Hypericum hookerianum Stem Against Ehrlich Ascites Carcinoma in Swiss Albino Mice

Abstract: Abstract. A large number of plants belonging to the Hypericum family are known to possess strong antitumor properties. The methanol extract of H. hookerianum WIGHT and ARNOTT stem (MEHH) exhibited potent in vitro cytotoxic activity against various cancerous cell lines. In the present study, the high performance liquid chromatography (HPLC) standardized MEHH was tested for in vivo antitumor properties against Ehrlich ascites carcinoma (EAC) tumor bearing mice at 100, 200, and 400 mg / kg body weight doses given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Previous studies have noted the bioactivies of the Hypericum genus including the antitumor, antioxidant, antimicrobial and natural killer (NK) cell-activating activity (8)(9)(10)(11)(12). HJT, an annual herb from the genus Hypericum L., known in traditional Chinese medicine as Tian-ji-huang, grows mainly throughout southern China.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted the bioactivies of the Hypericum genus including the antitumor, antioxidant, antimicrobial and natural killer (NK) cell-activating activity (8)(9)(10)(11)(12). HJT, an annual herb from the genus Hypericum L., known in traditional Chinese medicine as Tian-ji-huang, grows mainly throughout southern China.…”
Section: Discussionmentioning
confidence: 99%
“…Hypericum hookerianum is well known in folklore medicine for its different therapeutic potentials, including antidepressant, spasmolytic, stimulant, hypotensive and antifungal activities (Asolkar, Kakkar, & Chakre, 1992). In earlier studies, we reported the antitumour (Dongre, Badami, Natesan, & Raghu, 2007), cytotoxic (Vijayan et al, 2003) and CNS activities (Mukherjee, Suresh, & Verpoorte, 2001) of H. hookerianum. So far, antioxidant studies of this plant have not been reported.…”
Section: Introductionmentioning
confidence: 85%
“…A fraction of this extract displayed 60% cell growth inhibition at a concentration of 0.95 lg/ml (Skalkos et al 2005). Lately, Dongre et al (2007) reported antitumor activity of the methanol extract of Hypericum sp. against Ehrlich Ascites Carcinoma in swiss albino mice.…”
Section: Hypericum Perforatum Linnmentioning
confidence: 98%